Partakers of the divine nature: the history and development of deificiation in the Christian traditions - Christensen, Michael J.; Wittung, Jeffery A. (Fairleigh Dickinson University Press, 2007)
Part I. The Context of Theosis in Christianity: -- The problem, promise, and process of theosis / Michael J. Christensen -- The place of theosis in Orthodox theology / Andrew Louth -- Part II. Theosis in Classical and Late Antiquity: -- Deification of the philosopher in classical Greece / John R. Lenz -- Can we speak of theosis in Paul? / Stephen Finlan -- Does 2 Peter 1:4 speak of deification? / James Starr -- Part III. Theosis in Patristic Thought: -- The strategic adaptation of deification in the Cappadocians / J. A. McGuckin -- Rhetorical application of theosis in Greek patristic theoloy / Vladimir Kharmlamov -- Divinization as perichoretic embrace in Maximus the Confessor / Elena Vishnevskaya -- Paradise as the landscape of salvation in Ephrem the Syrian / Thomas Buchan -- Part IV. Theosis in Medieval and Reformation Thought: -- The Copto-Arabic tradition of theosis: a eucharistic reading of John 3:51-57 in Būluṣ al-Būshī's treatise on the incarnation / Stephen J. Davis -- St. Anselm: theoria and the doctrinal logic of perfection / Nathan R. Kerr -- Martin Luther: "Little Christs for the world"; faith and sacraments as means to theosis / Jonathan Linman -- John Calvin: united to God through Christ / J. Todd Billings -- John Wesley: Christian perfection as faith filled with the energy of love / Michael J. Christensen -- Part V. Theosis in Modern Thought: -- Neo-Palamism, divinizing grace, and the breach between East and West / Jeffrey D. Finich -- Sergius Bulgakov: Russian theosis / Boris Jakim -- Karl Rahner: divinization in Roman Catholicism / Francis J. Caponi -- Theosis in recent research: a renewal of interest and a need for clarity / Gösta Hallonsten -- Resources on theosis with select primary sources in translation / Jeffery A. Wittung